2021
DOI: 10.1109/access.2021.3119562
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Sensitive IOU Loss: An Improved Regression Loss Function in Remote Sensing Object Detection

Abstract: Regression loss function in object detection model plays a important factor during training procedure. The IoU based loss functions, such as CIOU loss, achieve remarkable performance, but still have some inherent shortages that may cause slow convergence speed. The paper proposes a Scale-Sensitive IOU(SIOU) loss for the object detection in multi-scale targets, especially the remote sensing images to solve the problem where the gradients of current loss functions tend to be smooth and cannot distinguish some sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…The IOU distance is calculated as the 1-IOU. For simplicity, this work uses the original IOU definition instead of any novel IOUs 24 , 49 – 51 , which may offer better performance but require more complicated computations. As a result, the value of the BPR improves from 11.4 to 99.9% with the ATT-YOLO design.…”
Section: Methodsmentioning
confidence: 99%
“…The IOU distance is calculated as the 1-IOU. For simplicity, this work uses the original IOU definition instead of any novel IOUs 24 , 49 – 51 , which may offer better performance but require more complicated computations. As a result, the value of the BPR improves from 11.4 to 99.9% with the ATT-YOLO design.…”
Section: Methodsmentioning
confidence: 99%
“…Most experiments [31][32][33] have shown that SIoU behaves well in the process of model training. That is the reason why it is introduced into the YOLOv7 model to form the final loss function together with other loss functions, with the formula of loss function exhibited in equation ( 15) where L conf , L cls , and L box and W denote the confidence loss, classification loss, locus box loss and their corresponding weights, respectively.…”
Section: Optimization In the Training Processmentioning
confidence: 99%
“…In object detection, the definition of the loss function has a significant impact on the final performance of the model [25][26][27]. In YOLOX, the GIoU (generalized intersection over union) [28] loss function is used as the localization loss function.…”
Section: Improvement Of Loss Functionmentioning
confidence: 99%